RUANG KOMUNITAS BERBASIS TANAMAN DI RAWA BELONG - Antonia Vicki Amelia; Suryono Herlambang (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Along with the times, there are more and more people, especially in big cities, who live individually and have less direct interaction between individuals, individuals with groups, and between groups. This lack of interaction is motivated by a variety of things, one of which is the absence of community spaces for gathering, interacting, or exchanging ideas. Plant as Connection is a plant-based community space located in the area of Rawa Belong, Kebon Jeruk, West Jakarta, with the aim of being a connector or link where individuals and groups can gather and interact directly. Due to its plant-based activities, this project is located in the Rawa Belong area, West Jakarta which has been known as an ornamental plant area from time immemorial. This project is designed based on plants because in the future life, plant is one of the important things that will affect the way of human life. The influence of plants on the human life has begun to be seen from the current conditions where many people are competing to planting at home to be used as room decoration, hobbies, leisure activities, even for consumption. Therefore, the similarity of activities and hobbies can lead to the emergence of new communities and create opportunities for community space to accommodate these community activities and increase interaction between individuals, individuals with groups, and between groups. Keywords:  community space; interaction; plants AbstrakSeiring perkembangan zaman semakin banyak orang-orang terutama di kota besar yang hidup secara individual dan kurang berinteraksi secara langsung baik antarindividu, individu dengan kelompok, maupun antar kelompok. Kurangnya interaksi tersebut dilatar belakangi oleh berbagai macam hal yang salah satunya adalah tidak adanya ruang-ruang komunitas untuk tempat berkumpul, berinteraksi, atau bertukar pikiran. Plant as Connection adalah sebuah ruang komunitas yang berbasis pada tanaman yang terletak di kawasan Rawa Belong, Kebon Jeruk, Jakarta Barat, dengan tujuan menjadi konektor atau penghubung dimana individu maupun kelompok dapat berkumpul dan berinteraksi secara langsung. Dikarenakan aktivitasnya yang berbasis pada tanaman, maka proyek ini berlokasi di kawasan Rawa Belong, Jakarta Barat yang sudah dikenal sebagai kawasan tanaman hias dari zaman dahulu. Proyek ini dirancang berbasis pada tanaman karena pada kehidupan di masa depan tanaman merupakan salah satu hal penting yang akan mempengaruhi cara hidup manusia. Pengaruh tanaman pada cara hidup manusia ini sudah mulai terlihat dari kondisi saat ini dimana banyak sekali orang yang berlomba-lomba untuk merawat tanaman di rumah guna dijadikan sebagai hiasan ruangan, hobi, aktivitas di kala senggang, bahkan untuk dikonsumsi. Oleh sebab itu, kesamaan aktivitas maupun hobi ini dapat mengakibatkan munculnya komunitas baru dan menciptakan peluang adanya ruang komunitas guna mewadahi aktivitas komunitas tersebut serta meningkatkan interaksi antarindividu, individu dengan kelompok, maupun antar kelompok.